Optical techniques for tracking multiple myeloma engraftment, growth, and response to therapy - Runnels, Judith M.; Carlson, Alicia L.; Pitsillides, Costas; Thompson, Brian D.; Wu, Juwell; Spencer, Joel A.; Kohler, John; Azab, Abdel Kareem; Moreau, Anne Sophie; Rodig, Scott; Kung, Andrew L.; Anderson, Kenneth Carl; et al. (My University, 2011)
Multiple myeloma (MM), the second most common hematological malignancy, initiates from a single site and spreads via circulation to multiple sites in the bone marrow (BM). Methods to track MM cells both in the BM and circulation would be useful for developing new therapeutic strategies to target MM cell spread. We describe the use of complementary optical techniques to track human MM cells expressing both bioluminescent and fluorescent reporters in a mouse xenograft model. Long-term tumor growth and response to therapy are monitored using bioluminescence imaging (BLI), while numbers of circulating tumor cells are detected by in-vivo flow cytometry. Intravital microscopy is used to detect early seeding of MM cells to the BM, as well as residual cancer cells that remain in the BM after the bulk of the tumor is eradicated following drug treatment. Thus, intravital microscopy provides a powerful, albeit invasive, means to study cellular processes in vivo at the very early stage of the disease process and at the very late stage of therapeutic intervention when the tumor burden is too small to be detected by other imaging methods
Keywords: Multiple myeloma; Bioluminescence; Confocal microscopy; Intravital imaging; In vivo cell tracking; In vivo flow cytometry